Composites Assembly for High Performance Fastener-Less Structures. - Yazdani Nezhad, Hamed (Institution of Engineering & Technology, 2023)
This book provides a broad and balanced span of information, covering both fundamentals and applications across academic and industrial state-of-the-art activities on assembly, joining and repair of high-performance structures made from fibre-reinforced polymer composites.
Keywords: Composite materials.; elektronické knihy; electronic books